Menuju Masyarakat Bebas Asam Urat Melalui Edukasi Pada Masyarakat di Gor Satria Purwokerto - Suandika, Made; Mukti, Refa Teja; Adhiansyah, Rama Bagus; Rahmadani, Retno Dea; Salsabila, Salwa Dwi (Yayasan Inspirasi El Burhani, 2025)
Introduction: Uric acid is a metabolic byproduct in the human body that must remain within normal limits to prevent adverse health effects. Elevated uric acid levels, known as hyperuricemia, are a major risk factor for gout or gouty arthritis, a form of rheumatic disease affecting the joints. This condition can impact not only the elderly but also individuals of productive age. Objective : To increase public awareness about the dangers of elevated uric acid levels and promote healthy lifestyle practices, including dietary management and physical activity, as preventive strategies against gout and related complications. Method : This awareness program involved nutrition counseling sessions focusing on purine-restricted diets, risk factor education, and lifestyle modification. Counseling materials were supported by evidence from medical literature and adapted for community understanding. Physical activity promotion included introducing regular exercise and aerobic routines as part of the daily schedule. The target audience was the general adult population, including those at risk for hyperuricemia. Result : Participants demonstrated increased knowledge regarding uric acid management, dietary risk factors, and the importance of regular exercise. Many reported positive changes in food choices and incorporation of physical activity into daily routines. Anecdotal feedback indicated greater motivation to maintain healthy habits and seek further medical advice when needed. Conclusion: Hyperuricemia poses significant health risks, including gout and cardiovascular complications. Nutrition counseling, combined with promotion of regular physical activity, is an effective strategy to improve community awareness and encourage sustainable lifestyle changes.